The changing politics of foreign policy - Hill, Christopher (New York : Palgrave MacMillan, 2003)
"This book is centrally concerned with the question of who and what foreign policy is - and should be - for. As such it will be of interest to the informed general reader as well as all those involved in the academic study of international relations."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: International relations -- Political aspects